Difference in the luminescence properties of orthorhombic and monoclinic forms of Y2GeO5:Ln (Ln = Tb3+ and Dy3+). (April 2015) - Tyagi, Adish; Shah, Alpa; Sudarsan, V.; Vatsa, R.K.; Jain, V.K.
Graphical abstract: Highlights: Improved emission colour purity with orthorhombic form of Y2 GeO5 . Non-stationary quenching exists in orthorhombic and monoclinic forms of Y2 GeO5 :Tb. Ion pair formation and cross relaxation quenching operating for Y2 GeO5 :Dy samples. Abstract: The luminescence properties of Tb 3+ and Dy 3+ doped orthorhombic and monoclinic forms of Y2 GeO5 are significantly different. Orthorhombic Y2 GeO5 doped with Tb 3+ and Dy 3+ ions gives bright green and blue emission upon UV light excitation with CIE coordinates (0.25, 0.46) and (0.25, 0.24), respectively. The monoclinic Y2 GeO5 doped with these ions exhibits light green and yellowish white emissions, respectively. This has been attributed to the differences in crystallographic environments around Y 3+ ions in orthorhombic and monoclinic forms of Y2 GeO5 . Quantum yield of emission for orthorhombic Y2 GeO5 :Tb (∼29%) is significantly higher than that of the monoclinic Y2 GeO5 :Tb (∼14%). Lifetime values corresponding to 4 F9/2 level of Dy 3+ ions in both monoclinic and orthorhombic forms of Y2 GeO5 follow an opposite trend with respect to 5 D4 level of Tb 3+ ions. This is attributed to difference in the concentration quenching mechanism operating for Tb 3+ and Dy 3+ ions.